(untitled) (Fiep Bulletin - online, 2012)
The purpose of this study was to determine the body mass index and the physical fitness of private school students in Santos- SP. Two hundred thirty one students (231 = 127 boys and 104 girls), ages between 4 and 10, performing the following tests: weight, height, horizontal jump, 21 yards run and medicine-ball throw. The results revealed that 51,1% of the boys and 55,7% of the girls are either overweight or obese. A significant difference was observed among the male students concerning the body composition measurements and the 21 yards running tests, the bigger the body composition measurement (overweight or obese), the worse test results. The same tendency was verified on the horizontal jump test for both genders. Children overweight and with high risk of obesity are usually less active. It happens because the low risk children have more body weight and there for and expending more energy to perform their activities. Considering the results, we may conclude that the children evaluated display a high level of overweight and a low level of physical fitness, witch justifies health care programs, specially the ones concerning physical activities.